Anniversary meeting: 30 November 1897 (Proceedings of the Society of Antiquaries of Scotland, 1898)
At the Anniversary meeting new Fellows were elected, including five new Honorary Fellows. A list of deceased Fellows was presented and the Annual report on the number of visitors and additions to the Society's museum. Meeting notes for 13 December, 1897 are appended.